Optimization of cell-surface exposed cytochrome in Shewanella oneidensis MR-1 (SOMR-1) for practical implementation of bioelectrochemical systems - Clerici, Giovanni Rusconi (2022)
"Bioelectrochemical systems (BESs) are unique devices capable to convert chemical energy into electrical energy (and vice-versa) through the metabolism of specific microorganisms, under anaerobic conditions. Extracellular electron transfer (EET) is the key metabolic trait that allows electroactive bacteria to connect their intracellular metabolism with external electron acceptors, including electrodes in BES. Shewanella oneidensis MR-1 (SOMR-1) is considered a model organism to study EET mechanism. In the absence of oxygen, the electrons generated in the cytoplasm by catabolic processes must flow outside of the cell envelope. (...)"